Feasibility of resistance training in adult McArdle patients: clinical outcomes and muscle strength and mass benefits - Santalla, Alfredo; Munguía-Izquierdo, Diego; Brea-Alejo, Lidia; Pagola-Aldazábal, Itziar; Díez-Bermejo, Jorge; Fleck, Steven J.; Ara, Ignacio; Lucia, Alejandro (Frontiers in Aging Neuroscience, 2014)
We analyzed the effects of a 4-month resistance (weight lifting) training program followed by a 2-month detraining period in 7 adult McArdle patients (5 female) on: muscle mass (assessed by DXA), strength, serum creatine kinase (CK) activity and clinical severity. Adherence to training was ≥ 84% in all patients and no major contraindication or side effect was noted during the training or strength assessment sessions. The training program had a significant impact on total and lower extremities’ lean mass (P<0.05 for the time effect), with mean values increasing with training by +855 g (95% confidence interval (CI): 30, 1679) and +547 g (95%CI: 116, 978), respectively, and significantly decreasing with detraining. Body fat showed no significant changes over the study period. Bench press and half-squat performance, expressed as the highest value of average muscle power (W) or force (N) in the concentric-repetition phase of both tests showed a consistent increase over the 4-month training period, and decreased with detraining. Yet muscle strength and power detraining values were significantly higher than pre-training values, indicating that a training effect was still present after detraining. Importantly, all the participants, with no exception, showed a clear gain in muscle strength after the 4-month training period, e.g., bench press: +52 W (95%CI: 13, 91); half-squat: +173 W (95%CI: 96, 251). No significant time effect (P>0.05) was noted for baseline or post strength assessment values of serum CK activity, which remained essentially within the range reported in our laboratory for McArdle patients. All the patients changed to a lower severity class with training, such that none of them were in the highest disease severity class (3) after the intervention and, as such, they did not have fixed muscle weakness after training. Clinical improvements were retained, in all but one patient, after detraining, such that after detraining all patients were classed as class 1 for